The Effect of Greater Auricular Nerve Block and Auriculotemporal Nerve Block on The Expression of Inflammatory Factors TNF-α and IL-6 in Mastoidectomy Surgery: A Randomized Controlled Trial - Ayudha, Rangga; Waloejo, Christrijogo Soemartono; Airlangga, Prananda Surya; Kriswidyatomo, Prihatma; Ahadiah, Titiek Hidayati (Journal of Neonatal Surgery, 2025)
Background: The immune system can be triggered to release different inflammatory mediators like TNF-α and IL-6 in response to trauma and surgical stress. These cytokines in the acute inflammatory reaction take 4 to 6 hours to elicit a response after the initial trigger and can last up to 24 hours. Greater auricular nerve (GAN) and auriculotemporal nerve (ATN) blocks with 0.5% ropivacaine local anaesthetic potentially suppress this inflammatory response. This study evaluates the effectiveness of these blocks on TNF-α and IL-6 expression in mastoidectomy, considering the crucial role of these cytokines in acute inflammatory responses. Methods: The study enrolled 36 patients scheduled for elective mastoidectomy between November 2024 and January 2025. General anesthesia was administered to all participants, while patients in the treatment arm also received greater auricular nerve (GAN) and auriculotemporal nerve (ATN) blocks. Inflammatory markers TNF-α and IL-6 were measured at two timepoints: after general anesthesia induction and following the surgical procedure. Statistical tests will use comparative tests. Results: The research indicated that GAN and ATN blocks utilizing 0.5% ropivacaine significantly mitigated the elevations of TNF-α and IL-6 after mastoidectomy. The block group exhibited no significant elevation in TNF-α (P=0.595) and IL-6 (P=0.420) postoperatively, while the control group demonstrated large elevations (p<0.001) in both markers. Postoperative levels of TNF-α (P<0.001) and IL-6 (P<0.001) exhibited substantial differences between groups, demonstrating the efficacy of GAN and ATN blocks in preventing and reducing the inflammatory response. Conclusion: GAN and ATN blocks with 0.5% ropivacaine in elective mastoidectomy significantly inhibit postoperative increases in TNF-α and IL-6 levels. The use of 0.5% ropivacaine demonstrates an anti-inflammatory effect in elective mastoidectomy surgery.